PHYTOCHEMICAL SCREENING AND GC-MS ANALYSIS OF ETHANOLIC EXTRACT OF Chromolaena odorata LEAVES - Aditya Candra; Tahara Dilla Santi; Ika Waraztuty; Syarifah Nora Andrianty; Andri; Said Aandy Saida (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Chromolaena odorata leaves are empirically known to act as anti-inflammatory and other pharmacological effects. In this study, ethanol extracts from Chromolaena odorata leaves were analyzed using phytochemical screening and gas chromatography-mass spectrometry (GC-MS) to identify phytochemical constituents. Phytochemical tests showed the presence of flavonoids, alkaloids, tannins, saponins, and phenolics. GC-MS analysis of ethanol extracts from Chromolaena odorata leaves detected the presence of seven phytochemical compounds, namely Ethyl (E)-4-(2-phenylethylamino)but-2-enoate; 2h-pyran 2-(7-heptadecynyloxy) tetrahydro; 3,7,11-Trimethyldodeca-2,6,10-trienyl acetate; Bicyclo(3.1.1)heptane, 2,6,6-trimethyl-,(1alpha,2beta,5alpha)-11,13-Dimethyl-12-tetradecen-1-yl acetate; (2E,7R,11R)-3,7,11,15-tetramethyl-2-hexadecen-1-ol, and 9,12,15-Octadecatrienoic acid. This study identified several constituents that are biologically active compounds through GC-MS. These phytocompounds have potential as herbal medicines due to pharmacological activities such as antioxidant, anti-inflammatory, antimicrobial, antibacterial, and anticancer.